Makna Inovasi Dalam Pandangan Pengurus Koperasi Se-Bandung Raya Pada Era Revolusi Industri 4.0 - Khaerul Syobar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
The purpose of this research is to find out what the meaning of innovation is in the view of cooperative administrators throughout Bandung Raya, especially in the era of the industrial revolution 4.0. This arises from the existence of increasingly fierce competition in innovating both regionally, nationally and internationally in the era of the industrial revolution 4.0. The research approach used is with qualitative research methods. Retrieval of data through interviews, observation and documentation. The results show that the meaning of innovation in the view of cooperative administrators in Bandung Raya, especially in the era of the industrial revolution 4.0, is threefold, namely: (1) innovation in the view of cooperative administrators throughout Bandung Raya as increasing productivity, (2) innovation in the view of cooperative administrators -Bandung Raya as customer needs, and (3) innovation in the view of cooperative administrators throughout Bandung Raya as a way to improve performance. The conclusion of this study is that innovation in the era of the industrial revolution 4.0 for cooperative managers throughout Bandung Raya is a necessity in order to maintain the existence of cooperatives in the era of the industrial revolution 4.0